Analysis of the Three Lines Model in Risk Management of Village Fund Procurement in East Kalimantan - Hanantio, Bio Audi; Djakman, Chaerul D. (E-Jurnal Akuntansi, 2025)
The procurement of goods and services (PBJ) funded by the Village Fund often faces high risks, including delays in implementation, nonconformity to specifications, and potential irregularities. These risks are largely due to weak internal control systems and a low understanding of risk management among village officials. This study examines how applying the Three-Line Model can improve risk management in XYZ Village's procurement process. A qualitative case study approach was employed, utilizing data collection techniques such as document review and semi-structured interviews with nine informants from the village government, the Department of Rural Development and Social Welfare (DPMDes), and the Regional Inspectorate. Data were collected from January to March 2025 and analyzed thematically using source triangulation. The results revealed that the three lines were not functioning optimally and lacked support from an integrated risk management system. This research empirically contributes to strengthening Village Fund governance by integratting risk management practices into the Three Lines Model framework. Keywords: Three Lines Model; Risk Management; Procurement of Goods and Services; Village Fund.